2012
DOI: 10.1117/12.974812
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the DIRCM engagement: component and system level performance

Abstract: The proliferation of a diversity of capable ManPADS missiles poses a serious threat to civil and military aviation. Aircraft self protection against missiles requires increased sophistication as missile capabilities increase. Recent advances in self protection include the use of directed infrared countermeasures (DIRCM), employing high power lamps or lasers as sources of infrared energy. The larger aircraft self-protection scenario, comprising the missile, aircraft and DIRCM hardware is a complex system. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Also, the radiance intensities corresponding to the min and max gray level are obtained using Equation (2). The radiance intensities corresponding to the gray levels between the min and max gray levels can be obtained based on the proportional relationship of the radiance intensity and gray level, and then temperatures corresponding to the obtained radi-ance intensities for the gray levels between min and max gray levels are estimated using Equation (6). Then, the approximately estimated temperature is compensated by using the slope information of original temperatureradiance curve and the approximated one.…”
Section: Proposed Ir Composite Image Generation Methods Using Temperatmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the radiance intensities corresponding to the min and max gray level are obtained using Equation (2). The radiance intensities corresponding to the gray levels between the min and max gray levels can be obtained based on the proportional relationship of the radiance intensity and gray level, and then temperatures corresponding to the obtained radi-ance intensities for the gray levels between min and max gray levels are estimated using Equation (6). Then, the approximately estimated temperature is compensated by using the slope information of original temperatureradiance curve and the approximated one.…”
Section: Proposed Ir Composite Image Generation Methods Using Temperatmentioning
confidence: 99%
“…We can know that the radiance intensity for the temperature and the temperature estimation error have different characteristics for each WB. Figure 4 shows the original radiance curve L * ðTÞ and approximately estimated one LðTÞ according to arbitrary temperature.T represents the estimated temperature obtained from the radiance LðTÞ using Equation (6). The compensated temperatureT obtained using only the first order tangent slope of L * ðTÞ forT is as follows:…”
Section: Journal Of Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of effective OCM techniques and their implementation into a system to protect a platform requires the analysis of the platform's susceptibility of being engaged by a missile in a hostile environment, accurate modelling of the behaviour of a launched missile, the evaluation of target detection and tracking algorithms, and the analysis of the sur- III vivability of the platform once a damage has occurred. Several conference papers and references therein provide unclassified data and models based on elementary physics as a starting point for further analysis [13,14,15,16,17,18].…”
Section: Optical Countermeasure Systemsmentioning
confidence: 99%
“…In addition, others showed that in-band laser radiance on an uncooled thermal imager leads to thermal runaway, causing damage before a significant number of pixels are dazzled 12 . Simulations of the interaction of laser dazzle with imagers are fundamental to gaining the most from experimental and trials data 13 . It is also vital to understand the impact of the focal plane array integration on the extent of laser dazzle 14 .…”
Section: Introductionmentioning
confidence: 99%